2022
DOI: 10.24833/2410-2423-2021-5-29-119-120
|View full text |Cite
|
Sign up to set email alerts
|

Some ideas on diversity, inclusion and metaphorization in polyglot studies

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The global relevance of these issues is highlighted by the fact of the UN declaring the years 2022-2032 the International Decade of Indigenous Languages. The presenter also indicated that polyglots can provide interesting data for the study of cognitive metaphors, which in many cases are not merely literary techniques but rather indispensable instruments of language and thinking as certain phenomena (even in science) can only be described metaphorically [4], [11].…”
mentioning
confidence: 99%
“…The global relevance of these issues is highlighted by the fact of the UN declaring the years 2022-2032 the International Decade of Indigenous Languages. The presenter also indicated that polyglots can provide interesting data for the study of cognitive metaphors, which in many cases are not merely literary techniques but rather indispensable instruments of language and thinking as certain phenomena (even in science) can only be described metaphorically [4], [11].…”
mentioning
confidence: 99%